2011
DOI: 10.1007/s12522-011-0088-3
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of female germ cells and ovarian tissues for fertility preservation

Abstract: To preserve the fertility of patients who undergo chemotherapy and/or radiotherapy, procedures for cryopreservation of female germ cells have been investigated. Cyropreservation methods differ according to follicle stage because the mammalian ovary contains a large number of oocytes at different growth stages. Follicles at very early stages, for example the primordial and primary stages, are usually cryopreserved within ovarian cortical tissue because they need surrounding somatic cells for subsequent developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 106 publications
(122 reference statements)
0
2
0
Order By: Relevance
“…Since the first success with vitrification of mouse embryos in 1972 (Whittingham et al, 1972), vitrification had been applied for preserving fertility in over twenty species, particularly in women with infertility or who are facing age‐related fertility decline (Cobo & Garcia‐Velasco, 2016). Oocyte vitrification has been proved to promote faster recovery of oocyte spindles (Hashimoto et al, 2011; Smith et al, 2010) and possesses a higher recovery rate than slow‐rate freezing ("Matur & e oocyte cryopreservation: a guideline, 2013). However, due to their high sensitivity, oocytes are vulnerable to mechanical or oxidative damage caused by vitrification (Palmerini et al, 2014), hindering the popularization of this technology.…”
Section: Introductionmentioning
confidence: 99%
“…Since the first success with vitrification of mouse embryos in 1972 (Whittingham et al, 1972), vitrification had been applied for preserving fertility in over twenty species, particularly in women with infertility or who are facing age‐related fertility decline (Cobo & Garcia‐Velasco, 2016). Oocyte vitrification has been proved to promote faster recovery of oocyte spindles (Hashimoto et al, 2011; Smith et al, 2010) and possesses a higher recovery rate than slow‐rate freezing ("Matur & e oocyte cryopreservation: a guideline, 2013). However, due to their high sensitivity, oocytes are vulnerable to mechanical or oxidative damage caused by vitrification (Palmerini et al, 2014), hindering the popularization of this technology.…”
Section: Introductionmentioning
confidence: 99%
“…DMSO and/or EG have been used as cryoprotectants for human ovarian tissue cryopreservation (Hashimoto et al, 2011;Isachenko et al, 2012;Kagawa et al, 2009); however, it has been revealed that DMSO, which is known to be an epimutagen, although having no effect on about 99% of the DNA methylation profile, alters the DNA methylation status with methylation and demethylation in some particular loci (Iwatani et al, 2006). Maternal toxicity was observed in oral intake of EG in animal.…”
Section: Discussionmentioning
confidence: 99%